Software Process Improvement and Capability Determination: 15th International Conference, SPICE 2015, Gothenburg, Sweden, June 16-17, 2015. Proceedings - Rout, Terry (Springer, 2015)
This book constitutes the refereed proceedings of the 15th International Conference on Software Process Improvement and Capability Determination, SPICE 2015, held in Gothenburg, Sweden, in June 2015. The 17 revised full papers presented together with three short papers were carefully reviewed and selected from 48 submissions. The papers are organized in topical sections on industrial frameworks; implementation and assessment; process improvement; agile processes; assessment and maturity models; process and education.